Integration of anti-PD-1 antibody into chemotherapeutic regimens improved the outcome of aggressive NK cell leukemia: a single-center retrospective real-world analysis - Shen, Kai; Liao, Yi; Dai, Yang; Ji, Jie; Kuang, Pu; Liu, Zhigang; Xie, Liping; Niu, Ting; Jiang, Nenggang; Ma, Hongbing (Frontiers in Immunology, 2025)
BackgroundAggressive natural killer (NK) cell leukemia (ANKL) is a rare NK cell neoplasm associated with Epstein-Barr virus (EBV) infection. Programmed cell death protein 1 (PD-1) blockade, which is successful in extranodal NK/T-cell lymphoma and EBV-related hemophagocytic lymphohistiocytosis, is considered to have a potential role in managing ANKL.ObjectivesThis study aims to characterize ANKL clinically and evaluate the prognostic impact of anti-PD-1 antibody treatment.MethodsWe retrospectively analyzed the clinical characteristics and treatment regimens of ANKL patients from March 2009 to October 2023 in a single center. Data on clinical characteristics, treatment regimens and prognosis were collected from medical records. Overall survival (OS) of different risk groups was analyzed by Kaplan-Meier method. The least absolute shrinkage and selection operator (LASSO)-penalized Cox regression was used to identify the potential prognostic factors of ANKL.ResultsFrom March 2009 to October 2023 a total of 71 ANKL were retrieved with an OS of 2.0 months. Seven patients (9.9%) received PD-1 antibodies combined with various chemotherapies; thirty-five patients (49.3%) received asparaginase as part of chemotherapy; and eight patients (11.3%) received allogeneic HSCT after induction chemotherapy. Among patients who did not undergo allogeneic hematopoietic stem transplantation (HSCT), patients who received PD-1 antibodies as part of chemotherapy exhibited a superior OS than those without PD-1 antibodies (5.4 vs 1.6 months, p=0.035). The 1-year OS rate was 43% in the PD-1 subgroup compared with only 4% in the non-PD-1 subgroup. LASSO-Cox multivariate analysis revealed that PD-1 antibodies-containing regimens were associated with better survival (hazard ratio [HR]=0.349, 95% CI: 0.145 0.840, p=0.019). So was it with HSCT and asparaginase (HR=0.267, 95% CI=0.101 0.701 and HR=0.355, 95% CI=0.206 0.613, respectively).ConclusionANKL still had a poor outcome in the past decade. Integration of anti-PD-1 antibody into chemotherapeutic therapy significantly improved the survival of ANKL. The prolonged survival attributed to PD-1 blockade could provide critical opportunities for patients awaiting HSCT.